Implementasi Pendekatan Teaching at The Right Level (TaRL) Untuk Meningkatkan Kemampuan Membaca dan MenulisDi Kelas I SD Negeri 060858 Medan - Maisyaroh Atika; Suci Perwita Sari (Journal on Education, 2024)
This research is a Classroom Action Research (CAR) which aims to improve students' reading and writing skills by implementing the Teaching at The Right Level (TaRL) approach assisted by flipbook learning media. The subjects in this study were 22 students of grade 1 of State Elementary School 060858 Medan. The percentage of students can be seen that there is an increase in the results of students' reading and writing skills from cycle I to cycle II in category group A (Proficient) paragraph level has an increase of 9.1%. The increase in the results of students' reading and writing skills from cycle I to cycle II in category group B (Quite Proficient) Syllable/Word level has an increase of 9.1%. The increase in the results of students' reading and writing skills from cycle I to cycle II in category group C (Need Guidance) Beginner/Letter level has an increase of 18.2%. There was an increase in students' reading and writing skills after being given learning with the Teach at The Right Level (TaRL) approach assisted by flipbook media. Thus, it can be concluded that learning using the Teach at The Right Level (TaRL) approach assisted by flipbook media can improve students' reading and writing skills according to their respective levels of understanding.